2014
DOI: 10.4049/jimmunol.1400594
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection Activates Src Homology-2 Domain–Containing Phosphatase 2 To Suppress IFN-γ Signaling

Abstract: Helicobacter pylori infection not only induces gastric inflammation but also increases the risk of gastric tumorigenesis. IFN-γ has antimicrobial effects; however, H. pylori infection elevates IFN-γ–mediated gastric inflammation and may suppress IFN-γ signaling as a strategy to avoid immune destruction through an as-yet-unknown mechanism. This study was aimed at investigating the mechanism of H. pylori–induced IFN-γ resistance. Postinfection of viable H. pylori decreased IFN-γ–activated signal transducers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…ELISA assays were performed to investigate the mechanism of synergistic benefits of combined therapy. Similar to current result, it has been reported that the levels of IFN-γ as a potent inflammatory cytokine was increased by H. pylori infection [30]. Attained data showed that curcumin (by direct anti-inflammatory and anti-microbial effects) and erythromycin (by decreasing the agent's induced inflammation), could regress the levels of cytokine.…”
Section: Discussionsupporting
confidence: 78%
“…ELISA assays were performed to investigate the mechanism of synergistic benefits of combined therapy. Similar to current result, it has been reported that the levels of IFN-γ as a potent inflammatory cytokine was increased by H. pylori infection [30]. Attained data showed that curcumin (by direct anti-inflammatory and anti-microbial effects) and erythromycin (by decreasing the agent's induced inflammation), could regress the levels of cytokine.…”
Section: Discussionsupporting
confidence: 78%
“…In both human gastric epithelial and monocytic cells, H. pylori inhibits IFNc signaling through activation of Src homology-2 domain-containing phosphatase (SHP)2, in CagA-and ROS-dependent manners [127], thus favoring gastric cancer development [128][129][130].…”
Section: Helicobacter Pylori Infectionmentioning
confidence: 99%
“…−, no activity; +, activity. To better explore the mechanisms of curcumin effects on this infection, IFN-γ, IL-4, and somatostatin represent good molecules for this purpose, as it is known that IFN-γ levels are elevated by H. pylori infection (28). IL-4 is an anti-inflammatory cytokine, unknown to be depressed by H. pylori (29) and somatostatin is a regulatory peptide needed for IL-4 mediated resolution of H. pylori-related gastritis (30).…”
Section: Vetvicka Et Al Effects Of Curcumin On H Pylori Page 4 Ofmentioning
confidence: 99%